Targeted Vagus Nerve Stimulation for Rehabilitation After Stroke - Engineer, Navzer D.; Kimberley, Teresa J.; Prudente, Cecília N.; Dawson, Jesse; Tarver, W. Brent; Hays, Seth A. (Frontiers in Neuroscience, 2019)
Stroke is a leading cause of disability worldwide. In approximately 60% of individuals, upper limb deficits persist six months after stroke. These deficits adversely affect functional use of the upper limb and restrict participation in day to day activities. An important goal of stroke rehabilitation is to improve the quality of life by restoring functional independence and participation in activities. Since upper limb deficits are one of the best predictors of quality of life after stroke, effective interventions targeting upper limb deficits may represent a means to improve quality of life. An increased understanding of the neurobiological processes underlying stroke recovery has led to the development of targeted approaches to improve motor deficits. One such targeted strategy uses brief bursts of Vagus Nerve Stimulation (VNS) paired with rehabilitation to enhance plasticity and support recovery of upper limb function after chronic stroke. Stimulation of the vagus nerve triggers release of plasticity promoting neuromodulators, such as acetylcholine and norepinephrine, throughout the cortex. Timed engagement of neuromodulators concurrent with motor training drives task-specific plasticity in the motor cortex to improve function and provides the basis for paired VNS therapy. A number of studies in preclinical models of ischemic stroke demonstrated that VNS paired with rehabilitative training significantly improved the recovery of forelimb motor function compared to equivalent rehabilitative training without VNS. The improvements were associated with synaptic reorganization of cortical motor networks and recruitment of residual motor neurons controlling the impaired forelimb, demonstrating the putative neurobiological mechanisms underlying recovery of motor function. These preclinical studies provided the basis for conducting two multisite, randomized controlled pilot trials in individuals with moderate to severe upper limb weakness after chronic ischemic stroke. VNS paired with rehabilitation improved motor deficits compared to rehabilitation alone. The trials provided support for a 120-patient pivotal study designed to evaluate the efficacy of VNS paired with rehabilitation in individuals with chronic ischemic stroke. This review will discuss the neurobiological rationale for VNS therapy, examine the preclinical and clinical evidence of VNS therapy in the context of stroke, and outline the challenges and opportunities for the future use of VNS therapy.